IMPROVING THE ECONOMIC MECHANISM TO SUPPORT EXPORT POTENTIAL IN THE CONTEXT OF LIBERALIZATION OF THE FOREIGN EXCHANGE MARKET IN UZBEKISTAN (Euro-Asia Conferences, 2021)
The article considers the directions for the liberalization of the foreign exchange market in Uzbekistan, the identification of factors influencing the promotion of export potential, and thus the development of recommendations to support the export potential of enterprises.